Association of hip and pelvic geometry with tibiofemoral osteoarthritis: Multicenter Osteoarthritis Study (MOST) - Boissonneault, A; Lynch, J; Wise, B; Segal, N; Gross, K; Murray, D; Nevitt, M; Pandit, H (W.B. Saunders Ltd, 2014)
Objective: Lateral tibiofemoral osteoarthritis (OA) is overall less common than medial tibiofemoral OA, but it is more prevalent in women. This may be explained by sex differences in hip and pelvic geometry. The aim of this study is to explore sex differences in hip and pelvic geometry and determine if such parameters are associated with the presence of compartment-specific knee OA. Methods: This case-control study reports on 1,328 hips/knees from 664 participants and is an ancillary to the Multicenter Osteoarthritis Study (MOST). Of the 1,328 knees, 219 had lateral OA, 260 medial OA, and 849 no OA. Hip and pelvic measurements were taken from full-limb radiographs on the ipsilateral side of the knee of interest. After adjusting for covariates, means were compared between sexes and also between knees with medial and lateral OA vs no OA using separate regression models. Results: Women were shown to have a reduced femoral offset (FO) (mean 40.9 mm vs 45.9 mm; P = 0.001) and more valgus neck-shaft angle (mean 128.4° vs 125.9° P < 0.001) compared to men. Compared to those with no OA, knees with lateral OA were associated with a reduced FO (P = 0.012), increased height of hip centre (HHC) (P = 0.003), more valgus neck-shaft angle (P = 0.042), and increased abductor angle (P = 0.031). Knees with medial OA were associated with a more varus neck-shaft angle (P = 0.043) and a decreased abductor angle (P = 0.003). Conclusion: These data suggest anatomical variations at the hip and pelvis are associated with compartment-specific knee OA and may help to explain sex differences in patterns of knee OA. © 2014 Osteoarthritis Research Society International.